Preface: The 3rd International Electronic Conference on Nutrients - Maria Luz Fernandez; M. Luisa Bonet; Francisco J Pérez Cano; Egeria Scoditi (Biology and Life Sciences Forum, 2024)
The Third International Electronic Conference on Nutrients—Precision Nutrition and Nutrigenomics was held from 1 to 15 November 2023 [...]